Tinjauan Literatur: Perkembangan Water Based Coolant Beraditif Mxene, Carboxymethyl Cellulose, dan Span 60 Untuk Proses Pembubutan Baja AISI 1045 Menggunakan Pahat Karbida Berlapis A LITERATURE REVIEW: DEVELOPMENT OF MXENE, CARBOXYMETHYL CELLULOSE, AND SP - Dikki Yumarsa (GLOBAL SCIENTS PUBLISHER, 2026)
Cutting fluid plays a vital role in conventional machining processes, particularly in controlling heat, friction, and tool wear during turning operations. The machining industry's continued reliance on oil-based coolants raises several concerns, including high operational costs, adverse health effects on operators, and environmental pollution from non-biodegradable waste. Water-Based Coolant (WBC) has emerged as a more environmentally friendly alternative, although its cooling and lubrication performance still requires enhancement through functional additives. This article presents a systematic literature review on the development of additive-based WBC formulated with MXene as a superior thermal conductor, Carboxymethyl Cellulose (CMC) as a thickening and stabilizing agent, and Span 60 as a nonionic emulsifier, particularly in the context of turning AISI 1045 steel using coated carbide cutting tools. Through the review and synthesis of eighteen references, this study maps the working mechanisms of each additive, the empirical findings of previous studies on surface roughness and tool wear, and the research gap that underlies the need for further experimental investigation under a Minimum Quantity Lubrication (MQL) system. This review is expected to serve as a conceptual and empirical foundation for experimental research on additive WBC formulations as an efficient, economical, and sustainable cooling solution.